2023
DOI: 10.3324/haematol.2023.283209
|View full text |Cite
|
Sign up to set email alerts
|

<i>BCL3</i> rearrangements in B-cell lymphoid neoplasms occur in two breakpoint clusters associated with different diseases

Abstract: The t(14;19)(q32;q13) often juxtaposes BCL3 with IGH resulting in overexpression of the gene. In contrast to other oncogenic translocations, BCL3-rearrangement (BCL3-R) has been associated with a broad spectrum of lymphoid neoplasms. Here we report an integrative whole-genome sequence, transcriptomic, and DNA methylation analysis of 13 lymphoid neoplasms with BCL3-R. The resolution of the breakpoints at single base-pair revealed that they occur in two clusters at 5’ (n=9) and 3’ (n=4) regions of BCL3 associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…Indeed, a recent study using next-generation sequencing (NGS) found rearrangements of upstream CEACAM16 and downstream CBLC and BCAM with IGH . 19 However, in cases with the latter two rearrangements, the tumors showed marginal zone lymphoma histopathology and lacked expression of BCL3, being clearly different from cases in our study. Bright nuclear staining of BCL3 by IHC observed in cases 3 and 4 suggests that, even though the (14;19)(q32;q13) breakpoints in these two cases were not within the same region as those in cases 1 and 2, they still occurred in the vicinity of BCL3 , resulting in the high level expression of the gene product under the influence of juxtaposed IGH .…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…Indeed, a recent study using next-generation sequencing (NGS) found rearrangements of upstream CEACAM16 and downstream CBLC and BCAM with IGH . 19 However, in cases with the latter two rearrangements, the tumors showed marginal zone lymphoma histopathology and lacked expression of BCL3, being clearly different from cases in our study. Bright nuclear staining of BCL3 by IHC observed in cases 3 and 4 suggests that, even though the (14;19)(q32;q13) breakpoints in these two cases were not within the same region as those in cases 1 and 2, they still occurred in the vicinity of BCL3 , resulting in the high level expression of the gene product under the influence of juxtaposed IGH .…”
Section: Discussioncontrasting
confidence: 88%
“…However, IGHD and IDHJ breakpoints were identified in a NGS-based study, 30 and switch regions associated with IGHG1 , IGHG2 , and IGHG3 were also affected in another study. 19 Currently, it is unclear whether the preferential Sα involvement observed in our series was due to a bias in case selection or difference in methods between us and others. Nevertheless, the presence of t(14;19)(q32;q13) and t(2;14)(p13;q32), the latter of which also involved Sγ2 switch regions and, therefore, was considered to be mediated by erroneous CSR mechanisms, 27 , 28 in IGHV -unmutated B-cell tumor cells supports the possibility that CSR can occur outside the germinal center in a T-cell-independent manner and before the initiation of somatic mutations in the IGH gene.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations